An inquiry into the teacher pupil interaction patterns in classes of PGDE teachers during their teaching practice - Karunasena, N.V. (My University, 2011)
Background of the Study In the Sri Lankan education system only about 750 complete junior secondary cycle and 250 students complete senior secondary cycle out of 1000 cohort who enters the Grade one. The low efficiency is due to many reasons. One reason may be the ineffectiveness of the teacher pupil interaction pattern. The students who do not achieve the expected level may not be identified by the teacher. As a result a retardation of students in their studies is possible. In a classroom the teacher interacts with the pupils personally by asking questions, discussing, and assigning tasks. Similarly student may ask questions from the teacher, show their work to the teacher. The opportunities of the diverse students to interact with the teacher seems to be unequal The researcher‘s interest is to find out how the interactions take place in the classroom. The class sizes are more than 40 in popular schools and close to 40 in many schools. It is difficult for a teacher to maintain equal interaction with all. The main objective was to identify the disparities of the interaction patterns relative to the seating area of the student. Methodology In this inquiry the inductive way of research is used. The data collection method was mainly observation. The researcher generalized the observation to identify patterns. The class area is divided into sub areas; Front area, Front right hand side area, Front left hand side area, Back right hand side area, Back left hand side area and Back area. At the beginning of observation the student seating arrangement was sketched. Different kinds of interactions were marked when such interaction occurred. For observations the teaching situations of PGDE trainee teachers assigned for evaluation were used during last two years. Specific sampling technique was not used. According to the situations during the supervision the observations related to the task ware carried out. Lessons of Science, Mathematics, Social science and Sinhala were observed. Outcomes of the Study It was observed that when providing visuals to student the teacher always gives the items to the student in the front rows. The Majority of questions were mostly asked from the student in the front rows. The student in the back right hand side and back left hand side were neglected. The student on the back right hand side and left hand side were backward in asking questions from the teacher too. This pattern deviates when a student who is attractive in anyway is seated in neglected areas. Seating area of student can be changed weekly as a remedy. The teacher has to be careful to identify his lapses and reduce the disparity. Training programmes have to be arranged to improve the teacher effectiveness.